Types and methods of publications - Taha Shadi T. (ХНУРЕ, 2023)
There are many different techniques that can be used in the publication process, depending on the type of publication you are working on and the specific requirements of your publisher or audience. The choice of each method, type and kind of publication is determined by the tasks facing researchers. For such a choice, it is also necessary to know the features of such publications. This work is devoted to a brief summary of the types and types of publications.
Keywords: Publication; knowledge